Pathogenesis of a variant in the 5′ untranslated region of ADAR1 in dyschromatosis symmetrica hereditaria. (27th January 2020) - Suganuma, Mutsumi; Kono, Michihiro; Yamanaka, Masayoshi; Akiyama, Masashi
Abstract: Dyschromatosis symmetrica hereditaria (DSH) is a pigmentary genodermatosis caused by mutations in ADAR1 . In this study, we performed mutation analysis on a family that included typical DSH patients. No mutations were found in any coding regions or exon–intron boundary regions of ADAR1, but a previously unreported non‐coding heterozygous variant, c.‐60A>G, was found in the 5′ untranslated region (5′UTR) of ADAR1 in the proband and her mother. The function of 5′UTR in mRNA is not well‐understood. To understand the pathogenesis of the variant and the function of the 5′UTR of ADAR1, we constructed two reporter genes carrying the ADAR1 5′UTR sequence with/without the variant between the PGK promoter and a luciferase coding sequence, and performed luciferase assays, semi‐quantitative PCR analyses, and polysomal assays. In human melanocytes, c.‐60A>G induced a 16% reduction in transcription and a 51% reduction in translation. Our results indicate that the 5′UTR c.‐60A>G variant adversely affects the post‐transcriptional step in gene expression, leading to DSH. Detailed functional assays of the 5′UTR of ADAR1 in the present study revealed the gene expression to be not only downregulated, but also upregulated by defects in 5′UTR depending on the locations. The regulation of translation by 5′UTR is very complicated.